Modulation of metabolic and immunoregulatory pathways in the gut transcriptome of Atlantic salmon (Salmo salar L.) after early nutritional programming during first feeding with plant-based diet - Tawfik, Marwa Mamdouh; Betancor, Mónica B.; McMillan, Stuart; Norambuena, Fernando; Tocher, Douglas R.; Douglas, Alex; Martin, Samuel A. M. (Frontiers in Immunology, 2024)
Plant-based nutritional programming is the concept of exposing fish at very early life stages to a plant-based diet for a short duration to improve physiological responses when exposed to a similar plant-rich diet at a later developmental stage. The mechanisms of action underlying nutritional programming have not been fully deciphered and the responses may be controlled at multiple levels. This 22-week study examines gut transcriptional changes after nutritional programming. Triplicate groups of Atlantic salmon are fed with a plant (V) vs. a marine-rich (M, control) diet for two weeks (stimulus phase) at first exogenous feeding. Both stimulus fish groups (M and V fish) were then fed M diet for 12 weeks (intermediate phase) and lastly fed V diet (challenge phase) for 6 weeks generating two dietary regimes (MMV, VMV) across phases. This study used a whole transcriptome approach to analyse the effects of the V diet at the end of stimulus (short-term effects) and 22-weeks post first feeding (long-term effects). After stimulus, due to its developmental stage, the whole intestine was used, whereas after challenge, pyloric caeca, middle and distal intestine were examined. At the stimulus end, genes with increased expression in V fish enriched pathways including regulatory epigenetic responses and lipid metabolism whereas genes involved in innate immune response were downregulated. In middle intestine at end of the challenge, expression levels of genes of lipid, carbohydrate, and energy metabolism were increased in V fish, whilst M fish revealed increased expression of genes associated with autoimmune and acute adaptive immune response. Distal intestine of V fish showed increased expression of genes associated with immune response and potential immune tolerance. Conversely, distal intestine of M fish at challenge revealed upregulation of lipid and carbohydrate metabolic pathways, tissue degeneration and apoptotic responses. The present study demonstrated nutritional programming-associated changes in the intestinal transcriptome, with altered expression of genes involved in both immune responses and different metabolic processes. While there were limited changes in growth between the groups, the results show that there were transcriptional differences suggesting a programming response, although the mechanism of this response still requires to be fully elucidated.